Lutas na cidade de São Paulo: Mutirão Recanto da Felicidade e Banco Comunitário União Sampaio - Bergamin, Marta de Aguiar (Universidade Federal de São Carlos, 2011)
The present work is aimed at exploiting the relationship between city and work, from the study of two democratic experiences: a self-managed joint effort (mutirão) and a community bank in the city of Sao Paulo. These two experiences show us that the social movements constantly need new ways of carrying out their actions in order to renew participation and strengthen the social organization towards the creation of a political community. Both the community bank, that broadens the range of the discussion on the endogenous circulation of money and on the possibility of higher consumption in the area, and the self-managed joint effort (mutirão), which intensifies the access to rights and to participation, are, however, experiences that struggle with huge difficulties and are perhaps weak as alternatives to the capitalist processes of sociability. In spite of that, they show themselves to be, in the very core of the system, capable of transforming previously precarious realities.
Keywords: Sociologia do trabalho; Cidades e vilas; Mutirão; Economia solidária; City; Work; Mutirão; Solidarity economy; Community bank; CIENCIAS HUMANAS::SOCIOLOGIA